Positive pole piece as well as preparation method and application thereof

By setting a gel ceramic layer at the edge of the ear side of the positive electrode sheet and constructing a gel electrolyte to lock the electrolyte, the problems of poor transmission of the electrolyte of the lithium-ion cell electrode sheet and lithium-ion cell electrode sheet are solved, and the cycling and safety performance of the cell is improved.

CN119695061APending Publication Date: 2025-03-25JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411856295.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

Smart Images

  • Figure HDA0005194284070000011
    Figure HDA0005194284070000011
Patent Text Reader

Abstract

The invention provides a positive pole piece as well as a preparation method and application thereof. The positive pole piece comprises a current collector, an active substance layer and a gel ceramic layer, wherein the current collector is coated with the active substance layer and the gel ceramic layer; the gel ceramic layer is connected with the active material layer and is arranged at the side edge of a tab of the positive pole piece; the gel ceramic layer comprises a gel electrolyte; the gel electrolyte is selected from polyoxyethylene, polymethyl methacrylate, polyacrylonitrile, hexafluoropropylene, polytetrahydrofuran and one or more of modified substances of the polyoxyethylene, the polymethyl methacrylate, the polyacrylonitrile, the hexafluoropropylene and the polytetrahydrofuran. Compared with the prior art, the positive pole piece provided by the invention has the advantages that the specific gel electrolyte is added into the ceramic layer at the top tab to form the gel ceramic layer, and the gel electrolyte is constructed in the gel ceramic layer, so that a part of electrolyte can be locked at the top of the battery cell pole piece, and the lithium ion transmission capability at the upper part of the pole piece is improved; therefore, lithium precipitation at the junction of the top of the anode and the top of the cathode plate is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and more specifically, to a positive electrode sheet and a preparation method and application thereof. Background Art

[0002] The battery cell is one of the basic units that make up the power battery. The core of the battery cell lies in the electrode. The electrode includes the current collector and the coating on the current collector. The coating is the positive electrode active material or the negative electrode active material, which directly participates in the electrochemical reaction of the battery to complete the storage and release of electrical energy.

[0003] However, due to the influence of gravity, the pole piece of the lithium-ion battery cell is prone to poor wetting on the pole ear side (the upper part of the pole piece), resulting in poor electrolyte infiltration on the upper part of the pole piece, thereby affecting the transmission of lithium ions in the electrolyte, causing lithium deposition, and affecting the cycle performance and safety performance of the battery cell. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a positive electrode plate and its preparation method and application. The positive electrode plate provided by the present invention can lock a portion of the electrolyte at the top of the battery cell plate, thereby improving the lithium ion transmission capacity of the upper part of the plate, thereby avoiding lithium deposition at the junction of the anode and cathode plates.

[0005] The present invention provides a positive electrode plate, comprising a current collector, an active material layer coated on the current collector and a gel ceramic layer; the gel ceramic layer is connected to the active material layer and is arranged at the edge position of the positive electrode plate ear side; the gel ceramic layer comprises a gel electrolyte; the gel electrolyte is selected from polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, hexafluoropropylene, polytetrahydrofuran, and one or more modified substances of the above substances.

[0006] Preferably, the gel ceramic layer further comprises a ceramic material and a binder, and the mass ratio of the ceramic material, the gel electrolyte and the binder in the gel ceramic layer is (10-80): (8-80): (10-12).

[0007] Preferably, the ceramic material is Al 2 O 3 and / or Al(OH) 3 , the binder is PVDF.

[0008] Preferably, the mass ratio of the ceramic material, the gel electrolyte and the binder is (20-60):(30-70):(10-12).

[0009] Preferably, the coating thickness of the gel ceramic layer is 10 μm to 70 μm.

[0010] Preferably, the width of the gel ceramic layer is 2 mm to 7 mm, and the overlapping area with the active material layer is 0 to 0.5 mm.

[0011] The present invention also provides a method for preparing the positive electrode sheet described in the above technical solution, comprising the following steps:

[0012] a) adding a ceramic material, a gel electrolyte and a binder into a solvent and mixing them to obtain a gel ceramic layer slurry; adding an active material, a conductive agent and a binder into a solvent and mixing them to obtain an active material layer slurry;

[0013] b) coating the gel ceramic layer slurry and the active material layer slurry obtained in step a) on the current collector, and obtaining the positive electrode sheet after drying.

[0014] Preferably, the mass ratio of the active material, the conductive agent and the binder in the active material layer slurry in step a) is (95-99): (0.5-2.5): (0.5-2.5).

[0015] Preferably, the solvent in step a) is NMP; the mixing method is stirring in a stirring kettle; the stirring temperature of the stirring kettle is 20°C to 30°C, the revolution speed of the stirring kettle is 10r / min to 20r / min, the rotation speed of the stirring kettle is 1400r / min to 1600r / min, and the stirring time is 1h to 10h.

[0016] The present invention also provides a lithium-ion battery, comprising a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the positive electrode plate is the positive electrode plate described in the above technical solution.

[0017] The present invention provides a positive electrode plate and a preparation method and application thereof; the positive electrode plate comprises a current collector, an active material layer coated on the current collector and a gel ceramic layer; the gel ceramic layer is in contact with the active material layer and is arranged at the edge of the positive electrode plate ear side; the gel ceramic layer comprises a gel electrolyte; the gel electrolyte is selected from polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, hexafluoropropylene, polytetrahydrofuran, and one or more modified substances of the above substances. Compared with the prior art, the positive electrode plate provided by the present invention forms a gel ceramic layer by adding a specific gel electrolyte to the ceramic layer at the top ear, and constructs a gel electrolyte in the gel ceramic layer, which can lock a part of the electrolyte at the top of the battery cell plate, thereby improving the lithium ion transmission capacity of the upper part of the plate, thereby avoiding lithium deposition at the junction of the anode and cathode plates.

[0018] In addition, the preparation method provided by the present invention does not change the current preparation process of the battery cell, the overall process is simple, easy to operate, the conditions are mild and easy to control, and it has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the relative positions of the gel ceramic layers in Example 1; wherein, 1: empty foil area (ear side), 2: gel ceramic layer, 3: active material layer. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The present invention provides a positive electrode plate, comprising a current collector, an active material layer coated on the current collector and a gel ceramic layer; the gel ceramic layer is connected to the active material layer and is arranged at the edge position of the positive electrode plate ear side; the gel ceramic layer comprises a gel electrolyte; the gel electrolyte is selected from polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, hexafluoropropylene, polytetrahydrofuran, and one or more modified substances of the above substances.

[0022] The purpose of the present invention is to provide a positive electrode plate design, which locks part of the electrolyte at the pole ear, thereby solving the lithium precipitation problem caused by insufficient kinetics on the upper part of the pole plate; on this basis, the technical solution of the present invention mainly includes: adding a gel electrolyte to the ceramic layer on the top of the cathode plate (positive electrode plate) to form a gel ceramic layer, constructing a gel electrolyte in the gel ceramic layer, locking the electrolyte to a certain extent, thereby providing kinetic support for the lithium ion transmission on the top of the pole plate in the later stage of the battery cell cycle.

[0023] The present invention has no special restrictions on the types and sources of the current collector and the active material layer, and the current collector and the active material layer for the positive electrode sheet well known to those skilled in the art can be used.

[0024] In the present invention, the gel ceramic layer is connected to the active material layer and is arranged at the edge of the positive electrode tab; the gel ceramic layer includes a gel electrolyte; the gel electrolyte is selected from polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), hexafluoropropylene (HFP), polytetrahydrofuran (PTHF), and one or more of the modified substances of the above substances, more preferably polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), hexafluoropropylene (HFP) or polytetrahydrofuran (PTHF). The present invention has no special restrictions on the source of the gel electrolyte, and commercially available products known to those skilled in the art can be used.

[0025] In the present invention, the gel ceramic layer preferably also includes a ceramic material and a binder, and the mass ratio of the ceramic material, the gel electrolyte and the binder in the gel ceramic layer is preferably (10-80): (8-80): (10-12), and more preferably (20-60): (30-70): (10-12).

[0026] In the present invention, the ceramic material is preferably Al 2 O 3 and / or Al(OH) 3 , more preferably Al 2 O 3 The binder is preferably PVDF. The present invention has no special restrictions on the sources of the ceramic material and the binder, and commercial products known to those skilled in the art can be used.

[0027] In a preferred embodiment of the present invention, the gel ceramic layer is prepared from a ceramic material, a gel electrolyte and PVDF in a mass ratio of (10-80): (8-80): (10-12), preferably from a ceramic material, a gel electrolyte and PVDF in a mass ratio of (20-60): (30-70): (10-12).

[0028] In the present invention, the coating thickness of the gel ceramic layer is preferably 10μm to 70μm, more preferably 20μm to 60μm, specifically 20μm±5μm, 30μm±5μm, 40μm±5μm, 50μm±5μm, 60μm±5μm ("±" represents the allowable control range of micron-level parameters). In the present invention, when the coating thickness of the gel ceramic layer is less than the lower limit of the above parameter range, the process is difficult to control and foil leakage is likely to occur. At the same time, the upper limit of the above parameter range is limited to make the thickness of the gel ceramic layer lower than the thickness of the active material layer to ensure the smooth progress of the process.

[0029] In the present invention, the width of the gel ceramic layer is preferably 2 mm to 7 mm, more preferably 4.5 mm to 5.5 mm, and specifically can be: 4.5 mm, 5 mm, 5.5 mm. In the present invention, the gel ceramic layer adopts the above width range, so that the edge of the pole piece and the ear side can be located on the gel ceramic layer, improving the safety performance; if the width is too wide, exceeding 7 mm, it will cause a waste of space and an increase in weight.

[0030] In the present invention, the overlap area between the gel ceramic layer and the active material layer is preferably 0-0.5 mm; if it is greater than 0.5 mm, it will affect the diffusion path of the active material under the gel ceramic layer, affecting the gram capacity, and at the same time, there will be a thick width area in the process, and the rolling process is prone to problems; and if it is less than 0 mm, the foil will leak.

[0031] In the present invention, the gel ceramic layer still retains the characteristic of improving the safety of the battery cell, and at the same time, can improve the liquid absorption capacity of the electrode, and provide kinetic support for lithium ions in the top area of ​​the electrode in the later stage of the battery cell.

[0032] The present invention also provides a method for preparing the positive electrode sheet described in the above technical solution, comprising the following steps:

[0033] a) adding a ceramic material, a gel electrolyte and a binder into a solvent and mixing them to obtain a gel ceramic layer slurry; adding an active material, a conductive agent and a binder into a solvent and mixing them to obtain an active material layer slurry;

[0034] b) coating the gel ceramic layer slurry and the active material layer slurry obtained in step a) on the current collector, and obtaining the positive electrode sheet after drying.

[0035] The present invention firstly adds a ceramic material, a gel electrolyte and a binder into a solvent and mixes them to obtain a gel ceramic layer slurry; and then adds an active material, a conductive agent and a binder into a solvent and mixes them to obtain an active material layer slurry. In the present invention, the ceramic material, the gel electrolyte and the binder are the same as those in the above technical solution and are not described in detail here.

[0036] In the present invention, the mass ratio of the active material, the conductive agent and the binder in the active material layer slurry is preferably (95-99): (0.5-2.5): (0.5-2.5), and more preferably (96-98): (0.5-1.5): (1.5-2.5). In a preferred embodiment of the present invention, the active material is preferably LFP; the conductive agent is preferably SP; and the binder is preferably PVDF. The present invention has no special restrictions on the types and sources of the active material, conductive agent and binder, and commercially available sources of active material layer slurry raw materials for preparing positive electrode sheets that are well known to those skilled in the art can be used.

[0037] In the present invention, the solvent is preferably NMP; a commercial source known to those skilled in the art can be used. The present invention has no special restrictions on the amount of the solvent, and a conventional amount known to those skilled in the art that can facilitate uniform mixing of the raw material components can be used. In a preferred embodiment of the present invention, the amount of the solvent is calculated based on the solid content of the gel ceramic layer slurry being 20% ​​to 40%.

[0038] In the present invention, the mixing method is preferably stirring in a stirring kettle; the stirring temperature of the stirring kettle is preferably 20°C to 30°C, the revolution speed of the stirring kettle is preferably 10r / min to 20r / min, the rotation speed of the stirring kettle is preferably 1400r / min to 1600r / min, and the stirring time is preferably 1h to 10h.

[0039] Finally, the present invention coats the obtained gel ceramic layer slurry and active material layer slurry on the current collector, and obtains the positive electrode sheet after drying.

[0040] In the present invention, the specific positions where the gel ceramic layer slurry and the active material layer slurry are coated on the current collector can be set according to the relative positions of the current collector, the active material layer and the gel ceramic layer in the above technical solution, and the present invention will not be repeated here. The present invention has no special restrictions on the coating and drying process, and can be achieved by using technical means for preparing positive electrode sheets well known to those skilled in the art.

[0041] The preparation method provided by the present invention does not change the current preparation process of the battery core, the overall process is simple, easy to operate, the conditions are mild and easy to control, and has broad application prospects.

[0042] The present invention also provides a lithium-ion battery, comprising a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the positive electrode plate is the positive electrode plate described in the above technical solution.

[0043] In the present invention, the negative electrode plate is prepared by a preparation method well known to those skilled in the art, preferably: the anode active material, conductive agent, binder and solvent are uniformly mixed to form an anode slurry, and the anode slurry is uniformly coated on the anode current collector to form an anode plate.

[0044] In the present invention, the preparation method of the lithium-ion battery preferably adopts: the positive electrode plate, the separator, the negative electrode plate, and the separator are assembled in sequence to obtain a bare cell, and the assembly method can be selected from lamination and winding, and the electrolyte is injected into the dried bare cell to obtain a lithium secondary battery.

[0045] In the present invention, the isolation membrane can be made of polyethylene film, polypropylene film, polyvinylidene fluoride film and non-woven fabric; the electrolyte includes lithium salt and solvent, wherein the types of lithium salt and solvent are not specifically limited and can be selected according to actual needs. For example, the lithium salt can be LiPF 6 、LiTFSI、LiBF 4 wait.

[0046] The present invention provides a positive electrode plate and a preparation method and application thereof; the positive electrode plate comprises a current collector, an active material layer coated on the current collector and a gel ceramic layer; the gel ceramic layer is in contact with the active material layer and is arranged at the edge of the positive electrode plate ear side; the gel ceramic layer comprises a gel electrolyte; the gel electrolyte is selected from polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, hexafluoropropylene, polytetrahydrofuran, and one or more modified substances of the above substances. Compared with the prior art, the positive electrode plate provided by the present invention forms a gel ceramic layer by adding a specific gel electrolyte to the ceramic layer at the top ear, and constructs a gel electrolyte in the gel ceramic layer, which can lock a part of the electrolyte at the top of the battery cell plate, thereby improving the lithium ion transmission capacity of the upper part of the plate, thereby avoiding lithium deposition at the junction of the anode and cathode plates.

[0047] In addition, the preparation method provided by the present invention does not change the current preparation process of the battery cell, the overall process is simple, easy to operate, the conditions are mild and easy to control, and it has broad application prospects.

[0048] In order to further illustrate the present invention, the following examples are used to explain the present invention in detail. If no specific conditions are specified in the following examples of the present invention, the conventional conditions or the conditions recommended by the manufacturer are used; if the manufacturer of the reagents and instruments is not specified, they are all conventional products that can be purchased commercially; the raw materials used are all commercially available commodities.

[0049] Example 1

[0050] (1) Preparation process of positive electrode sheet:

[0051] Al 2 O 3 :PEO:PVDF=40:50:10 Add to NMP in proportion and stir evenly. Specifically, Al 2 O 3 : 12kg, PEO: 15kg, PVDF: 3kg, NMP: 70kg, added into a 60L stirring kettle, stirred at 25℃, revolution 15r / min, rotation 1500r / min, stirring time 2h, to obtain gel ceramic layer slurry.

[0052] Add LFP:SP:PVDF=97:1:2 to NMP in proportion, specifically, LPF: 194kg, SP: 2kg, PVDF: 4kg, NMP: 133kg, add into a 350L stirring kettle, stir at 25°C, revolution 15r / min, rotation 1500r / min, stirring time 8h, stir NMP evenly to obtain active material layer slurry.

[0053] The two slurries are evenly coated on the current collector aluminum foil, and the cathode electrode sheet (positive electrode sheet) is obtained after drying; wherein the area width of the gel ceramic layer is 5±0.5mm, the overlapping area with the membrane area is 0-0.5mm, and the thickness is 40±5μm; the relative position diagram of the gel ceramic layer is shown in Figure 1 As shown, 1 is the empty foil area (ear side), 2 is the gel ceramic layer, and 3 is the active material layer.

[0054] (2) Preparation process of negative electrode sheet:

[0055] Add graphite: SP: CMC: SBR = 96.5: 1: 1: 1.5 to water in proportion. Specifically, add 96.5 kg of graphite, 1 kg of CMC, 1 kg of SP, 1.5 kg of SBR and 100 kg of water into a 200 L stirring kettle. Stir at 25 ° C, orbital speed of 15 r / min, rotation speed of 1800 r / min, and stirring time of 8 h to obtain anode slurry. Evenly coat the anode slurry on the negative electrode copper foil and dry it to obtain the negative electrode sheet.

[0056] (3) The isolation film is made of polypropylene base film.

[0057] (4) During the cell assembly process, the positive electrode sheet, separator, negative electrode sheet, and separator are arranged in sequence, and the assembly method is winding.

[0058] (5) LiPF is used as electrolyte 6 It is dissolved in a solvent of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in a ratio of 1:1:1, with a concentration of 1.2 mol / L.

[0059] (6) Injecting the electrolyte into the dried battery cell, and obtaining a lithium-ion battery after formation and aging; wherein the battery cell is stored at room temperature of 25°C for 10 hours after injection, and stored at high temperature of 45°C for 10 hours; the formation current: 0.1C constant current charging to 3V, and then 0.3C constant current charging to 3.8V, the formation temperature is 45°C; the aging temperature is 45°C, and the aging time is 24 hours.

[0060] Example 2

[0061] The lithium ion battery is obtained by the preparation method provided in Example 1, the only difference being that the gel ceramic layer slurry is different, Al 2 O 3 :PEO:PVDF=60:30:10.

[0062] Example 3

[0063] The lithium ion battery is obtained by the preparation method provided in Example 1, the only difference being that the gel ceramic layer slurry is different, Al 2 O 3 :PEO:PVDF=20:70:10.

[0064] Example 4

[0065] A lithium ion battery was obtained by the preparation method provided in Example 1, the only difference being that the gel factor in the gel ceramic layer was different and the gel material was polymethyl methacrylate (PMMA).

[0066] Example 5

[0067] A lithium ion battery was obtained by the preparation method provided in Example 1, the only difference being that the gel factor in the gel ceramic layer was different and the gel material was polyacrylonitrile (PAN).

[0068] Example 6

[0069] A lithium ion battery was obtained by the preparation method provided in Example 1, the only difference being that the gel factor in the gel ceramic layer was different and the gel material was hexafluoropropylene (HFP).

[0070] Example 7

[0071] A lithium ion battery was obtained by the preparation method provided in Example 1, the only difference being that the gel factor in the gel ceramic layer was different and the gel material was polytetrahydrofuran (PTHF).

[0072] Example 8

[0073] A lithium ion battery was obtained by the preparation method provided in Example 1, the only difference being that the thickness of the gel ceramic layer was 20±5 μm.

[0074] Example 9

[0075] The lithium ion battery was obtained by the preparation method provided in Example 1, except that the thickness of the gel ceramic layer was 60±5 μm.

[0076] Comparative Example 1

[0077] The lithium ion battery was obtained by the preparation method provided in Example 1, except that the formula of the ceramic layer in Comparative Example 1 was ceramic (Al 2 O 3 ):PVDF=90:10, no gel electrolyte.

[0078] In Examples 1 to 9 and Comparative Example 1, the surface density of the negative electrode of the battery cell is 0.15 g / 1540.25 mm 2 The model of the aluminum shell used to make the battery cell is 52148, and the nominal capacity is 104Ah.

[0079] The performance of each lithium-ion battery was tested, and the results are shown in Table 1 below; wherein, the test method of the cycle performance is as follows: (1) standing for 30 minutes; (2) charging at 1C constant current and constant voltage to 3.65V, with a cut-off current of 0.05C; (3) standing for 30 minutes; (4) discharging at 1C constant current to 2.5V, recording the initial capacity, repeating the above operation until the discharge capacity is less than 80% of the initial capacity, and recording the number of cycles at this time.

[0080] DCR test method: (1) Stand still for 30 minutes; (2) Charge to 3.65V with 1C constant current and constant voltage, with a cut-off current of 0.05C; (3) Stand still for 30 minutes; (4) Discharge with 1C constant current for 30 minutes; (5) Stand still for 60 minutes; (6) Discharge with 2C constant current for 30 seconds. The voltage before 2C constant current discharge for 30 seconds is recorded as the starting voltage, and the voltage after 2C constant current discharge for 30 seconds is recorded as the end-of-discharge voltage. DCR is calculated as (end-of-discharge voltage - starting voltage) / current 2C.

[0081] Capacity test method: (1) Stand for 30 minutes; (2) Charge to 3.65V at 1C constant current and constant voltage, with a cut-off current of 0.05C; (3) Stand for 30 minutes; (4) Discharge to 2.5V at 1C constant current to obtain the discharge capacity; (5) Cycle (1) to (4) twice, and take the second discharge capacity as the capacity of the battery cell.

[0082] Table 1

[0083] The junction between the top of the anode and the cathode Ceramic layer width / mm Cycle performance / cycle Capacity / Ah DCR / mΩ Example 1 No lithium precipitation 5.0 3200 104.1 0.54 Example 2 No lithium precipitation 4.9 3000 104.0 0.55 Example 3 No lithium precipitation 4.9 3050 104.0 0.56 Example 4 No lithium precipitation 5.0 3000 104.1 0.54 Example 5 No lithium precipitation 5.1 3100 104.0 0.55 Example 6 No lithium precipitation 5.2 3150 104.1 0.54 Example 7 No lithium precipitation 4.9 3050 104.0 0.55 Example 8 No lithium precipitation 5.0 2980 104.0 0.56 Example 9 No lithium precipitation 4.9 3400 104.2 0.53 Comparative Example 1 Lithium Separation 5.0 2500 104.0 0.55

[0084] The experimental results show that, compared with Comparative Example 1, in Examples 1 to 9, no lithium deposition occurs on the top of the electrode, the capacity and DCR of the battery cell do not deteriorate, and the cycle performance of the battery cell is greatly improved.

[0085] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A positive electrode sheet, characterized in that: It includes a current collector, an active material layer coated on the current collector and a gel ceramic layer; the gel ceramic layer is connected to the active material layer and is arranged at the edge of the positive electrode tab side; the gel ceramic layer includes a gel electrolyte; the gel electrolyte is selected from polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, hexafluoropropylene, polytetrahydrofuran, and one or more modified substances of the above substances.

2. The positive electrode sheet according to claim 1, characterized in that: The gel ceramic layer also includes a ceramic material and a binder. The mass ratio of the ceramic material, the gel electrolyte and the binder in the gel ceramic layer is (10-80): (8-80): (10-12).

3. The positive electrode sheet according to claim 2, characterized in that: The ceramic material is Al2O3 and / or Al(OH)3, and the binder is PVDF.

4. The positive electrode sheet according to claim 2, characterized in that: The mass ratio of the ceramic material, the gel electrolyte and the binder is (20-60): (30-70): (10-12).

5. The positive electrode sheet according to claim 1, characterized in that: The coating thickness of the gel ceramic layer is 10 μm to 70 μm.

6. The positive electrode sheet according to claim 1, characterized in that: The width of the gel ceramic layer is 2 mm to 7 mm, and the overlapping area with the active material layer is 0 to 0.5 mm.

7. A method for preparing a positive electrode sheet according to any one of claims 1 to 6, characterized in that: The following steps are involved: a) adding a ceramic material, a gel electrolyte and a binder into a solvent and mixing them to obtain a gel ceramic layer slurry; adding an active material, a conductive agent and a binder into a solvent and mixing them to obtain an active material layer slurry; b) coating the gel ceramic layer slurry and the active material layer slurry obtained in step a) on the current collector, and obtaining the positive electrode sheet after drying.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the active material, the conductive agent and the binder in the active material layer slurry in step a) is (95-99): (0.5-2.5): (0.5-2.5).

9. The preparation method according to claim 7, characterized in that: The solvent in step a) is NMP; the mixing method is stirring in a stirring kettle; the stirring temperature of the stirring kettle is 20°C to 30°C, the revolution speed of the stirring kettle is 10r / min to 20r / min, the rotation speed of the stirring kettle is 1400r / min to 1600r / min, and the stirring time is 1h to 10h.

10. A lithium-ion battery, comprising a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode sheet is the positive electrode sheet according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Ceramic slurry, ceramic separator and lithium ion battery

    CN109728233A

  • Lithium ion battery pole part, preparation method thereof and lithium ion battery

    CN111342002A

  • Pole piece with uniform thickness of tab ceramic coating and preparation method thereof

    CN112490403A

  • Isolating membrane, lithium ion battery, battery module, battery pack and electric device

    CN115566361A

  • Negative pole piece, preparation method of negative pole piece and lithium battery

    CN116666564A